The Effect of Working Capital Efficiency, Liquidity and Firm Size on Profitability in The Infrastructure Sector Listed on The Indonesian Stock Exchange - Shafirra Thasa Oktaputri; Haryati Setyorini (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
This study investigates the relationship between profitability and working capital efficiency, liquidity, and business size. The efficiency of working capital is assessed by the turnover of working capital. The current ratio is used to gauge liquidity. Total firm size is determined by the ln of total assets. This study employs a sample of sixty annual reports from twelve infrastructure-sector businesses listed on the Indonesia Stock Exchange from 2016 to 2020. Method of multiple linear regression utilized in an analytical procedure. The findings demonstrated that working capital efficiency, liquidity, and business size had a substantial and negative impact on profitability. The test findings revealed a correlation between working capital efficiency, liquidity, and business size and profitability. The magnitude of the effect was 16,9%, while the remaining 83,1% was influenced by other factors outside this research.